2014
DOI: 10.1016/j.neuropsychologia.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of attention networks in childhood and early adulthood

Abstract: a b s t r a c tAttention has been related to functions of alerting, orienting, and executive control, which are associated with distinct brain networks. This study aimed at understanding the neural mechanisms underlying the development of attention functions during childhood. A total of 46 healthy 4-13-year-old children and 15 adults performed an adapted version of the Attention Network Task (ANT) while brain activation was registered with a high-density EEG system. Performance of the ANT revealed changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
67
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 86 publications
16
67
3
Order By: Relevance
“…In this study, we also found that P3/SP responses were stronger and slower on incongruent trials than in congruent trials of the Stroop and Flanker tasks during neural processing of conflict resolution, which is consistent with cognitive control theory and prior empirical findings (Liotti et al, 2000; Rueda et al, 2004; Jonkman, 2006; Smith et al, 2008; Abundis-Gutierrez et al, 2014). Hormone effects on P3/SP responses reflected a possible testosterone-driven pattern in the Stroop and Flanker tasks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we also found that P3/SP responses were stronger and slower on incongruent trials than in congruent trials of the Stroop and Flanker tasks during neural processing of conflict resolution, which is consistent with cognitive control theory and prior empirical findings (Liotti et al, 2000; Rueda et al, 2004; Jonkman, 2006; Smith et al, 2008; Abundis-Gutierrez et al, 2014). Hormone effects on P3/SP responses reflected a possible testosterone-driven pattern in the Stroop and Flanker tasks.…”
Section: Discussionsupporting
confidence: 91%
“…Conflict resolution is associated with the neural processing of resolution of the conflicts. The positive P3 and slow potential (SP) with central-parietal distribution correlate with conflict resolution (Liotti et al, 2000; Rueda et al, 2004; Jonkman, 2006; Smith et al, 2008; Abundis-Gutierrez et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that an inferior ability to utilize multisensory information for facilitation at a lower stimulus processing level may have impacted on children's ability to exploit this for the benefit of cognitive operations, such as the learning of novel multisensory associations. Immature attention capacities in children may have also contributed to this result (e.g., Abundis‐Gutierrez, Checa, Castellanos, & Rosario Rueda, ; Cromer, Schembri, Harel, & Maruff, ; Morrison, ; Pozuelos, Paz‐Alonso, Castillo, Fuentes, & Rueda, ), as multisensory processes have been shown to be dependent on an individual's state of attention (e.g., Dean et al., ; Hillyard, Stormer, Feng, Martinez, & McDonald, ; Talsma, ; Talsma, Senkowski, Soto‐Faraco, & Woldorff, ). Indeed, it is likely that the current task engaged significant attentional resources given the speeded nature of the task and the fact that an incidental trial‐and‐error learning paradigm was employed.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological (Abundis-Gutiérrez et al, 2014) and neuroimaging (Casey et al, 2000; Konrad et al, 2005) studies have shown that structural and functional changes in the brain support this development.…”
Section: Introductionmentioning
confidence: 99%